2017
DOI: 10.1186/s12891-017-1691-1
|View full text |Cite
|
Sign up to set email alerts
|

With a biomechanical treatment in knee osteoarthritis, less knee pain did not correlate with synovitis reduction

Abstract: BackgroundBraces are used to treat pain in patellofemoral joint osteoarthritis (PFJOA). In a trial, we previously reported pain improvement after 6-weeks brace use. The pain reduction did not correlate with changes in Magnetic Resonance Imaging (MRI) assessed Bone Marrow Lesion volume or static synovial volume. Studies show that changes in the synovium on dynamic contrast enhanced (DCE) MRI are more closely associated with symptom change than static synovial volume changes. We hypothesised change in synovitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…However, pain symptoms are often observed before signs of inflammation are present in a joint developing RA, and increased pain sensitivity of non-inflamed sites has been observed in RA patients (Lee et al., 2009), while synovitis and pain do not always correlate (Forslind & Svensson, 2016). This discrepancy between inflammation and pain was also found in knee OA patients, where pain intensity poorly correlated with the degree of inflammation (Siebuhr et al., 2014; Petersen et al., 2016; Swaminathan et al., 2017; Riis et al., 2017). This may be related to the observation that both in RA and OA, pain can arise from pain signals by the peripheral (joint), spinal and supraspinal pain pathways (Zhang & Lee, 2018; O'Neill & Felson, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…However, pain symptoms are often observed before signs of inflammation are present in a joint developing RA, and increased pain sensitivity of non-inflamed sites has been observed in RA patients (Lee et al., 2009), while synovitis and pain do not always correlate (Forslind & Svensson, 2016). This discrepancy between inflammation and pain was also found in knee OA patients, where pain intensity poorly correlated with the degree of inflammation (Siebuhr et al., 2014; Petersen et al., 2016; Swaminathan et al., 2017; Riis et al., 2017). This may be related to the observation that both in RA and OA, pain can arise from pain signals by the peripheral (joint), spinal and supraspinal pain pathways (Zhang & Lee, 2018; O'Neill & Felson, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, other studies, using imaging modalities for synovitis assessment, have shown associations between inflammation and clinical outcomes 7,11 . Furthermore, synovitis is known to fluctuate, and this fluctuation has shown correlations to fluctuations in clinical outcomes 25,26 , although conflicting evidence exists 27,28 . The discrepancy with our results may be caused by the fact that inflammation was only assessed once, while clinical aspects were assessed multiple times during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Posteriormente, con la ayuda de las respuestas del cuestionario se tomó en consideración la ubicación de la vivienda y poder adquisitivo, con lo cual se pudo manejar un programa de recomendaciones centrado en el paciente con el mayor aprovechamiento del entorno en todos los niveles. 21,22 Valoración sicológica Los diagnósticos fueron obtenidos de la primera intervención mediante entrevista clínica y cuestionario. 23,24,25 Y para la última evaluación se utilizó la escala clinimétrica de Yessavage y la entrevista clínica.…”
Section: Valoración Socialunclassified